Paraneoplastic Limbic Encephalitis Complicated with Small Cell Lung Cancer at the Time of Recurrence - Hironori Sadamatsu; Yuki Kurihara; Koichiro Takahashi; Kazutoshi Komiya; Shinsuke Ogusu; Haruki Hirakawa; Hiroki Tashiro; Chiho Nakashima; Tomomi Nakamura; Naoko Sueoka-Aragane (Case Reports in Oncology, 2019)
Paraneoplastic limbic encephalitis (PLE) is a rare neurologic disorder that can complicate various malignancies, including lung cancer. PLE is most frequently found the initial presentation of lung cancer. In this study, we reported the case of a 74-year-old Japanese woman who developed PLE after partial remission of small cell lung cancer (SCLC) by first-line systemic chemotherapy. Brain magnetic resonance imaging showed no metastatic tumor or cerebrovascular disease. Anti-glutamic acid decarboxylase (GAD) and anti-amphiphysin antibodies were detected in her serum. She was diagnosed as having PLE related to the recurrence of SCLC and received high-dose glucocorticoid, and sequentially systemic chemotherapy with amrubicin. Unfortunately, these treatments did not improve her disease progression and she died 4 months later. Although PLE rarely occurs at the time of SCLC recurrence, physicians should pay attention to PLE onset even after chemotherapy.